Pengaruh Model Pembelajaran Discovery Learning Terhadap Kemampuan Menulis Teks Eksposisi Siswa Kelas XII SMAN 8 Makassar - Maratus Shalihah; Iin Nur Yasinta (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
The effect of the discovery learning learning model on the ability to write exposition texts for grade XII students of SMAN 8 Makassar. The expected research objective is that this study aims to determine the influence of the discovery learning learning model on writing ability in the exposition texts of grade XII students of SMAN 8 Makassar. This research is a quantitative descriptive research. The technique used to collect data for this research is a test technique. The test instrument is used to determine the ability to write exposition texts of students. The results showed that the average score of students' ability to write exposition texts before using the learning model was 69.5. After being treated using the discovery learning model, the average score obtained by students was 80.2. The results of the hypothesis test with inferential statistics (t-test) independent samples test) stated that the research hypothesis was accepted because of the t-calculated t-value of >the t-table (6000>1,690). The improvement in the ability to write explanatory texts using the learning model was 78%, which was previously 41% without using the learning model. In other words, there is an influence of the discovery learning learning model on the ability to write expository texts for grade XII students of SMA Negeri 8 Makassar.